Short-Term Test–Retest Reliability of Contralateral Suppression of Click-Evoked Otoacoustic Emissions in Normal-Hearing Subjects - Keppler, Hannah; Degeest, Sofie; Vinck, Bart (Journal of speech, language, and hearing research, 2021)
Purpose: The objective of the current study was to investigate the short-term test-retest reliability of contralateral suppression (CS) of click-evoked otoacoustic emissions (CEOAEs) using commercially available otoacoustic emission equipment. Method: Twenty-three young normal-hearing subjects were tested. An otoscopic evaluation, admittance measures, pure-tone audiometry, measurements of CEOAEs without and with contralateral acoustic stimulation (CAS) to determine CS were performed at baseline (n = 23), an immediate retest without and with refitting of the probe (only CS of CEOAEs; n = 11), and a retest after 1 week (n = 23) were performed. Test-retest reliability parameters were determined on CEOAE response amplitudes without and with CAS, and on raw and normalized CS indices between baseline and the other test moments. Results: Repeated-measures analysis of variance indicated no random or systematic changes in CEOAE response amplitudes without and with CAS, and in raw and normalized CS indices between the test moments. Moderate-to-high intraclass correlation coefficients with mostly high significant between-subjects variability between baseline and each consecutive test moment were found for CEOAE response amplitude without and with CAS, and for the raw and normalized CS indices. Other reliability parameters deteriorated between CEOAE response amplitudes with CAS as compared to without CAS, between baseline and retest with probe refitting, and after 1 week, as well as for frequency-specific raw and normalized CS indices as compared to global CS indices. Conclusions: There was considerable variability in raw and normalized CS indices as measured using CEOAEs with CAS using commercially available otoacoustic emission equipment. More research is needed to optimize the measurement of CS of CEOAEs and to reduce influencing factors, as well as to make generalization of test-retest reliability data possible.